United States census collection
Manuscript abstract of the census of 1800 listing the four most populous cities in each state and towns in which newspapers were published; list (circa 1867) estimating population by state according to race; excerpt from the annual report (1904) of the secretary of the interior summarizing records of censuses from 1790 to 1890; and twenty-four state census schedules (1790-1820).
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Department of the Interior; American newspapers -- History; United States -- Census; United States -- Population